Correlation analysis between mild cognitive impairment and the traditional Chinese medicine body constitution types among the elderly in a community in Changning District, Shanghai - XU Lei; ZHANG Min; WANG Wenwen; YU Li; ZHU Xuting; LYU Xiaorui (Shanghai yufang yixue)
ObjectiveTo investigate the correlation between mild cognitive impairment (MCI) and traditional Chinese medicine (TCM) body constitution types in the elderly, and to provide an evidence for the control of cognitive impairment in the elderly.MethodsThe elderly aged 65 and above who participated in the community physical examinations in a community of Changning District, Shanghai were selected as the research subjects. The cognitive function was assessed by using the Clock Drawing Test combined with the Ascertain Dementia 8-item Questionnaire (AD8), the Montreal Cognitive Assessment (MoCA) and the Mini-mental State Examination (MMSE). The diagnostic criteria for MCI was identified based on the 2018 Chinese Guidelines for the Diagnosis and Treatment of Dementia and Cognitive Disorders, along with the assessment results and clinical history information. The current investigation method was used to collect the basic information and the prevalence of chronic disease of the subjects through questionnaire inquiries. The elderly subjects’ ability to take care of themselves was evaluated based on the Elderly Self⁃Care Ability Evaluation Scale, while the TCM body constitution types were determined based on the Chinese Medicine Health Care Management Service Specification. The association of the detection rate of MCI with gender, education level, history of chronic disease and TCM body constitution types were analyzed lastly.ResultsA total of 2 351 elderly people were investigated, including 1 037 males and 1 314 females, with an average age of (74.11±6.15) years. 174 subjects, accounting for 7.40%, were identified with MCI. The highest detection rate of MCI in the elderly are those with a Qi stagnation constitution (10.8%), followed by those with a dampness-heat constitution (9.1%) and a Qi deficiency constitution (8.4%). Multivariate logistic regression analysis showed that advanced age, lower educational level, a history of tuberculosis, and TCM constitutions such as dampness-heat, Qi stagnation, and Qi deficiency were the potential risk factors for MCI.ConclusionThere is a significant association between TCM constitution types such as dampness-heat, Qi stagnation, and Qi deficiency with MCI. TCM techniques can be integrated into the health management services for the elderly population, and targeted interventions can be provided to those with imbalanced constitution types so as to reduce the risk of MCI.